Pre-monsoon Thunderstorm Season Climatology of Convective Available Potential Energy (CAPE) and Convective Inhibition (CIN) over Eastern India (MAUSAM, 2022)
The present work analyses climatological variations of Convective Available Potential Energy (CAPE) and Convective Inhibition (CIN) over the eastern India (Odisha, West Bengal and Jharkhand) during the pre-monsoon season, where thunderstorms are frequent and disastrous. The work utilises European Centre for Medium-Range Weather Forecast (ECMWF) reanalysis data: ERA-5 for 1987-2016, supplemented with information about thunderstorm occurrences over the region from India Meteorological Department (IMD). The CAPE and CIN values can differentiate thunderstorm days (TD) from non-thunderstorm days (NTD), with favourable conditions of convective weather on days of thunderstorms over the region, evident by CAPE and CIN. The coastal areas of Odisha and West Bengal, along with the Jharkhand bordering the northern West Bengal region, have higher CAPE and lower CIN values. The trend analysis of CAPE and CIN has been performed using the non-parametric Mann-Kendall test, which shows an apparent transformation of indices over time for different regions of states for TD and NTD. CAPE shows an increasing trend over the coastal districts of Odisha and West Bengal during TD and for the whole of West Bengal during 12 UTC NTD. The NTD cases show a decreasing trend over Odisha (both 00 and 12 UTC) and 00 UTC over West Bengal. CIN shows an increasing trend for TD and decreasing trend for NTD over whole Odisha, whereas, for West Bengal, trends are positive for coastal regions during TD and negative on the entire state during NTD. For Jharkhand, both the CAPE and CIN values show an increasing trend over the state during NTD, whereas for TD, both increasing/decreasing trends are visible. The analysis complements the observations of thunderstorm occurrence over the region to understand areas with higher potential of thunderstorm occurrence during pre-monsoon season.